Strategi Pengembangan Kerajinan Rotan di Desa Sungai Limas Kecamatan Haur Gading Kabupaten Hulu Sungai Utara - Purna Kusumayana; Ahmad Syarif (Rawa Sains: Jurnal Sains STIPER Amuntai, 2015)
This study aims to determine the strengths, weaknesses, opportunities and threats in the development of handicrafts in the Sungai Limas village of Hulu Sungai Utara, and alternative development strategies in the Sungai Limas village of Hulu Sungai Utara. Based on the results obtained from the analysis of IFE matrix total score of 2.767 and EFE matrices obtained a total score of 2.939 where the matrix V IE placed on the strategic quadrant keep and maintain (hold and maintain). Strategies that can be applied to this position is a strategic market penetration and product development